Governance and the IAS: in search of resilience - Dar, R. K. (ed.) (New Delhi, 1999)
This book contains the introspections, experiences and ideas exchanged by a group of IAS officials. The aim of the book is to bring the debate on the role of bureaucracy to the forefront and to draw out an agenda for change.
Keywords: IAS as an author